ASHES OBSCURING HORIZONS AND REVEALING DISCOURSES: : THE COLLECTIVE PERCEPTION OF THE ENVIRONMENTAL CRISIS OF WILDFIRES IN A PUBLIC OPINION SURVEY CONDUCTED IN RIO GRANDE DO SUL (Interdisciplinary Studies Journal, 2025)
This article critically and discursively analyzes the perceptions and feelings caused by the image entitled Dawn by ash under the old Guajuvira, captured in the context of recent burning in Brazilian biomes, in 2024. The research is based on the social theory of Fairclough discourse, to interpret the answers obtained through a form in Google Forms. The structure of the article unravels its driving questions, formed from questions: what is the image and what the image is, what it means and to whom they said and what they said about it. The investigative instrument included six closed and open questions directed at 15 participants, focusing on emotional reactions, attitudes and environmental concerns. The analysis follows the three -dimensional model of Fairclough, at three levels: description of linguistic phenomena in the responses, interpretation of discourses, and critical examination of underlying ideologies. Research is justified by the relevance of understanding how images that expose environmental impacts mobilize society and can foster conscious and unconscious actions in the face of climate change and environmental degradation.
Keywords: Critical Discourse Analysis; Sustainable Development; Three-Dimensional Theory